Drg s: The Counterrevolution in Financing Health Care - Dolenc, Danielle A. (The Hastings Center report, 1985)
DRGs may contain costs, but they threaten to restrict access to health care, to compromise its quality, and to impede the development of new medical technologies. Immediate corrections are necessary to ensure that hospitals continue to serve the poorest and sickest.